Kecurangan Akademik Mahasiswa dengan Mengintegrasikan Konsep Fraud Triangle dan Self Efficacy - Ni Made Rai Juniariani; Putu Dian Pradnyanitasari (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
Academic fraud is an act that reflects the absence of values of justice in it and ignores the value of honesty and violation of the rules committed by students to gain an advantage against themselves in the form of academic success. This study aims to explain thoroughly the academic fraud that occurs in the field influenced by fraud triangle, namely pressure, opportunity, rationalization and self efficacy. This study used 376 samples, namely accounting students from private universities in Bali. Determination of the sample using the Slovin formula and data collection techniques is done by distributing questionnaires to the survey method. To answer the research hypothesis using an analysis tool that is Moderated Regression Analysis. The results showed that the fraud triangle had a positive effect on student academic fraud and self efficacy weakened the effect of fraud traingle on student academic fraud.